ANALISIS PENGARUH LINGKUNGAN SEKOLAH TERHADAP PENINGKATAN KREATIVITAS SISWA SD NEGERI PULO IE KECAMATAN KUALA KABUPATEN NAGAN RAYA - Munazir; Nurjannah; Febry Fahreza (LPPM Universitas Cipta Mandiri, 2026)
This study aims to examine the inﬂuence of the school environment on enhancing the creativity of students at SD Negeri Pulo Ie, Kecamatan Kuala, Kabupaten Nagan Raya. The research subjects were 12 fourth-grade students, and data were collected using observation, interviews, validation, and documentation techniques. The results indicate that a supportive school environment and effective interpersonal communication have a positive and significant impact on teacher creativity. Support in the form of policies, school culture, and resources, along with teachers’ ability to communicate effectively with students, colleagues, and staff, encourages higher levels of teacher creativity in designing learning activities.